Gas heating: furnaces, boilers, controls, components - Obrzut, Jason (Mount Prospect, IL : ESCO Institute, 2019)
Depending on what part of the country that you reside in, gas-burning heating systems can be either an absolute necessity or a rarity. For those that maintain, service and install gas heating systems or those just looking for a more in-depth source of accurate information, this modular training program focuses on furnaces and boilers that burn natural gas or LP. The combustion of gas to generate heat can be dangerous and should be thoroughly understood by HVAC technicians. This program covers many facets of gas heating including: combustion, system components and controls, heating sequences, installation, and troubleshooting. This manual provides students and practicing technicians with the information and knowledge necessary to safely work on systems that incorporate gas combustion to provide heat. The information to service, maintain, and install these systems is also presented in an easy-to-understand format. The manual is full of color images and diagrams and includes end-of-chapter worksheets. The spiral binding textbook will allow students to tear out worksheets for grading by the instructor.
Chapter 1. Safety -- Chapter 2. Fuels and their properties -- Chapter 3. Combustion -- Chapter 4. Fuel System Components -- Chapter 5. Venting -- Chapter 6. Electrical Components and Controls -- Chapter 7. Gas-Fired Furnance Wiring Diagrams and Sequence of Operations -- Chapter 8. Gas-Fired Boiler Wiring Diagrams and and Sequence of Operations -- Chapter 9. Gas Pipe Sizing -- Chapter 10. Installation -- Chapter 11. Troubleshooting
Keywords: GAS AS FUEL